Separatisme di Asia Tenggara: Antara Penguasa dan Gerakan Nasionalis Kelompok Minoritas - Khairu Roojiqien Sobandi (Jurnal Kajian Wilayah, 2011)
This paper examine the existence of separatism in Southeast Asia, specifically, the interactions between state approaches in dealing with nationalist movements. The question is on how the identity of the Pattani Southern Thailand, Acehnese in Indonesia and Moro in the Philippines created and how state approaches contend with the movements. The aims of this paper are explaining these movements identity creation through historical experiences over centuries, and state approaches challenge the movements. The result shows that Moros and Acehnese identity formed through their conflicting historical journeys with kolonialists. However, Pattani identity constructed through history of Buddist rulers that also full of conflicts with Thai Muslim society. The values that referred on these three communities basically are ethno-nationalist shared with Islamic values. These communities are facing state repressions through military and bureaucracy policies, which only meet dead ends by the existence of conflicts. Pattani movement oppressed by Budhist Thailand acted discriminatively on Muslim community because of politics of differences of ethno-religion. The Thai rulers label Pattani as Islamic terrorist group. Likewise, the Philippines governerment fuels conflicts by demonizing Moros as same as Abu Sayyaf terrorist group. The Indonesian government did on the other side of the coin, which is not to demonize Acehnese as terrorist group when they have chance to did so and even after tsunami in 2004, they manage Helsinki agreement in 2005. It suggested that these three governments use multicultural nation approaches in dealing with the movements, which accommodate pluralist and multicultural identities on a more equal position.